2014
DOI: 10.4161/mabs.34454
|View full text |Cite
|
Sign up to set email alerts
|

VEGF neutralizing aerosol therapy in primary pulmonary adenocarcinoma with K-ras activating-mutations

Abstract: y Nathalie Heuz e-Vourc'h and Marie Wislez equally contributed to the study design and are co-senior authors of this article.Keywords: Non-small cell lung cancer, lung adenocarcinoma, anti-VEGF, monoclonal antibody, aerosol, K-ras mutation, anti-angiogenic agent, airways delivery, pharmacokinetics K-ras mutations promote angiogenesis in lung cancer and contribute to the drug resistance of cancer cells. It is not clear whether K-ras mutated adenocarcinomas are sensitive to anti-angiogenic therapy with monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…23 Moreover, local delivery of an anti-VEGF MAb to K-ras-induced adenocarcinoma-bearing lungs efficiently reduced tumor burden at »100-fold lower serum concentration of MAb than that after systemic delivery. 24 To our knowledge, ours is the first study to evaluate this route in administering an antibody to deplete a suppressive immune population. Our data indicate that while MDSC depletion by the nebulized antibody did not enhance NK cell recruitment induced by CpG-ODN/Poly(I:C), depletion did lead to increased NK cell activation, possibly by minimizing direct inhibition of these effector cells and/or by enhancing the ability of aerosolized CpG-ODN/Poly(I:C)-activated macrophages to promote NK cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Moreover, local delivery of an anti-VEGF MAb to K-ras-induced adenocarcinoma-bearing lungs efficiently reduced tumor burden at »100-fold lower serum concentration of MAb than that after systemic delivery. 24 To our knowledge, ours is the first study to evaluate this route in administering an antibody to deplete a suppressive immune population. Our data indicate that while MDSC depletion by the nebulized antibody did not enhance NK cell recruitment induced by CpG-ODN/Poly(I:C), depletion did lead to increased NK cell activation, possibly by minimizing direct inhibition of these effector cells and/or by enhancing the ability of aerosolized CpG-ODN/Poly(I:C)-activated macrophages to promote NK cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The MAb RB6-8C5 was administered endotracheally. 22,24 Briefly, mice were anesthetized and given 25 mg/ mouse of RB6-8C5 MAb using a Microsprayer Aerosolizer Model IA-1C connected to a FMJ-250 high-pressure syringe (Penn-Century, Philadelphia, PA, USA) introduced just before the first trachea bifurcation. 32 In all experiments, mice were weighed twice weekly, euthanized at the end of experiments and macroscopic lung metastases counted.…”
Section: Mice and Experimental Protocolsmentioning
confidence: 99%
“…anti-cancer agents and anti-fungals) or excipients at single or repeated doses, to assess efficacy, tolerance and PK (Chandenier et al, 2009;Frédéric Gagnadoux et al, 2005;Gagnadoux et al, 2008;Maillet et al, 2011;Montharu et al, 2010). The Microsprayer™ device has been used with success to assess the efficacy of several mAbs in murine models Hervé et al, 2014;Maillet et al, 2011). It should be noted however that tolerability issues have been raised concerning intratracheal administration with these devices in small rodents (slight and transitory lung inflammation (Dubois et al, 2013;Montharu et al, 2010) and lung lesions (Guillon et al, 2012)).…”
Section: Intra-tracheal Aerosol Deliverymentioning
confidence: 99%
“…To demonstrate that mAbs delivery through the airways is both feasible and relevant, Dr Heuz e-Vourc'h's team developed 2 animal models of lung cancer to test aerosol delivery of cetuximab (an approved antiepidermal growth factor receptor antibody), 9 and of an antimurine vascular endothelial growth factor antibody. 10 The results of both studies indicated that airway-delivered mAbs reach their target antigen in the tumor and are pharmacologically efficient in limiting tumor growth. Moreover, pharmacokinetics of the different mAbs delivered through the airways in mice and non-human-primates showed a limited lungs-tobloodstream passage and an accumulation of the antibodies in the lungs.…”
Section: Session 1: Administration Routesmentioning
confidence: 90%